2014
DOI: 10.7872/cryb.v35.iss3.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Based on PCR Methods: A Guideline for Mosses

Abstract: In recent years, the number of studies concerning population genetics and phylogenetics in mosses using molecular markers has remarkably grown. This review summarizes the main features of the most used molecular techniques based on PCR and their application in bryology, with particular attention to mosses. This work also provides a bibliographic guide to 108 molecular studies focused on mosses to assist in choosing the most suitable markers according to the main aims of a specific researc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…DNA amplification was performed by using 20 different ISSR primers with anchor sequence (Table 3) selected after initial screening in a set of 40. Anchor sequence offers the advantage to avoid the sliding of the primer along the repeated motif, which would lead to the formation of products of different lengths in the same locus, giving rise to confusing results and an overestimation of the variability [15].…”
Section: Dna Extraction and Issr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA amplification was performed by using 20 different ISSR primers with anchor sequence (Table 3) selected after initial screening in a set of 40. Anchor sequence offers the advantage to avoid the sliding of the primer along the repeated motif, which would lead to the formation of products of different lengths in the same locus, giving rise to confusing results and an overestimation of the variability [15].…”
Section: Dna Extraction and Issr Amplificationmentioning
confidence: 99%
“…Among experimental approaches to detect genotoxicity, multi-locus molecular markers provide an easy and fast method, since they do not require sequence information. Particularly, Inter Simple Sequence Repeats (ISSR), used in the present work, are more reliable than Random Amplified Polymorphic DNA (RAPD) because they use longer primers and higher annealing temperatures compared to the latter [15]. Several studies have demonstrated that growth inhibition under heavy metal stress in plants is particularly pronounced during seed germination at the early stages of seedling growth, e.g., [1,16] since the competition between heavy metal ions and the essential nutrient cations for binding and absorption by the root surface seem more active at the early growth stages.…”
Section: Introductionmentioning
confidence: 99%